ANALISIS TINGGI MUKA AIR PADA KAWASAN SUNGAI CILIWUNG MT. HARYONO – PINTU AIR MANGGARAI DENGAN PROGRAM HEC-RAS 5.0.3 - Joan Arnold Fredrik; Teddy W Sudinda; Wahyu Sejati (Universitas Trisakti, 2021)
Flooding in DKI Jakarta Province has become a routine that occurs every year. One of the causes of flooding in Jakarta is the overflow of the Ciliwung river. On February 20, 2021, flooding occurred around the MT herd. Haryono – Manggarai sluice as a result of overflowing water from the Ciliwung river. This study aims to identify the water level in the Ciliwung MT river area. Haryono – Manggarai Sluice using the HSS Nakayasu method and hydraulics analysis using the HEC-RAS 4.1.0 application. Based on the results of the analysis and studies that have been carried out in the Ciliwung MT river area. Haryono – Manggarai Sluice, the design flood discharge is obtained as follows: flood discharge 2 years return period = 198.08 m3/second, 5 year return period = 287.87 m3/second, 10 year return period = 351.12 m3/second, 25 year return period = 427.94 m3/sec, 50 year return period = 490.28 m3/sec, and 100 year return period = 563.44 m3/sec. The results of these calculations were analyzed using the HEC-RAS 4.1.0 program so that it can be seen that several points have the elevation of the water level exceeding the elevation of the river bank being targeted.